Successful pacing profiles of Olympic and IAAF World Championship middle-distance runners across qualifying rounds and finals - Hanley, B.; Stellingwerff, T.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: This was the first study to analyze high-resolution pacing data from multiple global championships, allowing for deeper and rigorous analysis of pacing and tactical profiles in elite-standard middle-distance racing. The aim of this study was to analyze successful and unsuccessful middle-distance pacing profiles and variability across qualifying rounds and finals. Methods: Finishing and 100-m-split speeds and season`s best times were collected for 265 men and 218 women competing in 800- and 1500-m races, with pace variability expressed using coefficient of variation. Results: In both events, successful athletes generally separated themselves from slower athletes in the final 200 m, not by speeding up but by avoiding slowing compared with competitors. This was despite different pacing profiles between events in the earlier part of the race preceding the end spurt. Approximately 10% of athletes ran season`s best times, showing a tactical approach to elite-standard middle-distance racing and possible fatigue across rounds. Men`s and women`s pacing profiles were remarkably similar within each event, but the previously undescribed seahorse-shaped profile in the 800-m (predominantly positive pacing) differed from the J-shaped negative pacing of the 1500-m. Pacing variability was high compared with world records, especially in the finals (coefficient of variation: 5.2-9.1%), showing that athletes need to be able to vary pace and cope with surges. Conclusions: The best athletes had the physiological capacity to vary pace and respond to surges through successive competition rounds. In competition-specific training, coaches should incorporate several sessions in which pace changes frequently and sometimes unexpectedly.